A New Spectral Class of Brown Dwarfs at the Bottom of the IMF in IC 348 - K. L. Luhman; C. Alves de Oliveira (The Astrophysical Journal Letters)
In a previous study, we used James Webb Space Telescope (JWST) to identify three new brown dwarfs in the center of a nearby star-forming cluster, IC 348. The faintest object had an estimated mass of 3–4 M _Jup , making it a contender for the least massive brown dwarf confirmed with spectroscopy. Two of the new brown dwarfs also exhibited absorption features from an unidentified aliphatic hydrocarbon, which were not predicted by atmospheric models and were not previously detected in atmospheres outside of the solar system. We have used JWST to perform a deeper survey for brown dwarfs across a larger field in IC 348. We have identified 39 brown dwarf candidates in NIRCam images and have obtained spectra for 15 of them with Near-Infrared Spectrograph (NIRSpec), nine of which are classified as substellar members of the cluster. The faintest new members have mass estimates of ∼2 M _Jup , providing a new constraint on the minimum mass of the IMF. Two new members (∼2 and 10 M _Jup ) exhibit large excess emission from circumstellar disks, demonstrating that they harbor the raw materials for planet formation. Finally, eight of the nine new brown dwarfs and one known member that is newly observed with NIRSpec show the aforementioned hydrocarbon features. Among the total of 11 brown dwarfs in IC 348 that have hydrocarbon detections, the features are stronger at fainter magnitudes, indicating that the hydrocarbon is a natural constituent of the atmospheres of the coolest newborn brown dwarfs. We propose a new spectral class “H” that is defined by the presence of the 3.4 μ m fundamental band of the hydrocarbon.